Stylistyka czy retoryka w wypowiedziach dziennikarskich? O błędzie w nazewnictwie, który ma konsekwencje semantyczne - Lichański, Jakub Z. (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The confusion between stylistics and rhetoric is widespread, not only among journalists, but also researchers who do not fully understand the scope of these two fields of linguistics. The aim of this text is to demonstrate how this confusion leads to the sense of a text being erroneously interpreted. It analyses various statements by journalists where this confusion leads to semantic misunderstandings. It thus leads not to errors, but to twisting the meaning of texts and creating a false view of reality. In conclusion, the author suggests we should learn better the differences between the two forms; only in this way can we provide the audience with accurate information.